Sevket Sureyya Aydemir and National Leftist Approach - Yilmaz, Eray (HACETTEPE UNIV, 2012)
Sevket Sureyya Aydemir is known with his studies on history. In the meantime he was a political figure who strived for impressing the Kemalist regime in 1930's through his political magazine called Kadro. He would have liked to approach Kemalism from a leftist perspective by putting special emphasis on etatism and cultural nationalism. Nevertheless, he was incapable of that. Following his unsuccessful attempt, he dedicated himself to studies on history. In the course of rising leftist policies in the 1960's he again appeared on magazines and newspapers with his comments on those leftist policies in the national approach. Thus, this study aims to evaluate his national leftist approach generally by taking some differences between the referred periods into account.
Keywords: Sevket Sureyya Aydemir; Kadro; National Leftism; Revolution; Principles of Turkish Socialism; History